PREVALENCE OF MALNUTRITION AND IMPACT ON POSTOPERATIVE OUTCOMES IN GASTROINTESTINAL CANCER SURGERY: A RETROSPECTIVE STUDY - Dr. Aswathi VM; Dr. Bonny A Joseph; Dr. Nizamudheen M Pareekutty; Reena C; Dr. Satheesan Balasubramanian (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Malnutrition is a prevalent and often under recognized factor in the cancer patients. It significantly influences treatment tolerance and clinical outcomes. This study aims to determine the prevalence of malnutrition in GI cancer using the Subjective Global Assessment (SGA) and to evaluate its association with post-operative morbidity in GI cancer patients. Methods: A retrospective observational study of 180 patients who underwent curative intent surgery in GI cancer at a tertiary cancer center in South India between January 2022 and December 2023 was done. Preoperative postoperative nutritional status was analyzed using SGA, and anthropometric and biochemical values. Post operative complications were graded as per Clavien-Dindo classification. Results: At presentation, 44% of patients had malnutrition (SGA B or C). They were older, more advances stage, lower BMI, albumin and hemoglobin levels compared to patients without malnutrition (SGA A). 30-daypost operative complication was slightly higher in malnourished patients (40% vs 20%, p value 0.002). Major post operative complications were higher in malnourished patients (25% vs 8%, p value 0.001). Malnourished patients had longer hospital stay and higher readmission rates. Nutrition status was significantly improved upon post treatment follow up after nutritional rehabilitation with improvements in weight, albumin and hemoglobin levels. Conclusions: Malnutrition is common in GI Cancer patients and it has a significant effect on major post operative complications and prolonged recovery. SGA is a valuable and practical tool for nutritional assessment and risk stratification. Nutrition screening must be routinely employed and aggressively managed in the management of GI cancers.